Angelina's baby sister - Holabird, Katharine (Holabird, Katharine. Angelina Ballerina., 2021)
"Angelina Ballerina thinks she's the luckiest mouse in the world; she's going to be a big sister! But being a big sister means change, and sometimes change can be hard. When her baby sister arrives, Angelina feels like no one has time for her anymore. They only want to fuss over Polly"--